The Effect of Gamification towards repurchase intention in e-commerce platform with Technology Advancement Model (TAM) as a Moderating Variable. - Clarissa Listya Susilo (FEB Universitas Sam Ratulangi Manado, 2022)
Abstract. Indonesia has the 4th most populous country in this world has a lot of potential for e-commerce businesses, this can be seen by the emergence of different e-commerce platform such as Tokopedia, Shopee, Bli Bli and many others. This statement is further supported by the fact that 26,5% of the population in Indonesia is comprised of the Z Generation, a generation which utilises technology on a daily basis including purchasing goods and making payments. When it comes to marketing effort, e-commerce platform utilises several strategies in order to attract someone to make a repurchase. One of the strategy that is commonly used by e-commerce platform is gamification. Therefore, this research aims to understand the relationship between gamification and repurchase intention in Shopee as an e-commerce platform. Since e-commerce platform require the user to use technology such as smart phone, this research also aims to understand the relationship between TAM and repurchase intention, as well as the moderating effect of TAM in the relationship between gamification and repurchase intention. This research utilises SEM-PLS to analyse the data that was gathered using questionnaire. The result of this research showed that gamification didn’t have a significant effect towards repurchase intention. While TAM has a significant effect towards repurchase intention. Last but not least, from the research result can be seen that TAM didn’t moderate the relationship between gamification and repurchase intention in Shopee as an e-commerce platform.Abstrak. Indonesia yang merupakan negara terpadat ke-4 di dunia ini memiliki banyak potensi untuk bisnis e-commerce, hal ini dapat dilihat dengan munculnya berbagai platform e-commerce seperti Tokopedia, Shopee, Bli Bli dan masih banyak lagi yang lainnya. Pernyataan ini juga didukung oleh fakta bahwa 26,5% penduduk Indonesia adalah Generasi Z, generasi yang sehari-hari memanfaatkan teknologi termasuk membeli barang dan melakukan pembayaran. Dalam hal upaya pemasaran, platform e-commerce menggunakan beberapa strategi untuk menarik seseorang untuk melakukan pembelian kembali. Salah satu strategi yang umum digunakan oleh platform e-commerce adalah gamification. Oleh karena itu, penelitian ini bertujuan untuk mengetahui hubungan antara gamification dan repurchase intention pada Shopee sebagai platform e-commerce. Karena platform e-commerce mengharuskan pengguna untuk menggunakan teknologi seperti ponsel pintar, penelitian ini juga bertujuan untuk memahami hubungan antara TAM dan niat beli ulang, serta efek moderasi TAM dalam hubungan antara gamifikasi dan niat beli ulang. Penelitian ini menggunakan SEM-PLS untuk menganalisis data yang dikumpulkan dengan menggunakan kuesioner. Hasil penelitian menunjukkan bahwa gamifikasi tidak berpengaruh signifikan terhadap niat beli ulang. Sedangkan TAM berpengaruh signifikan terhadap niat beli ulang. Last but not least, dari hasil penelitian terlihat bahwa TAM tidak memoderasi hubungan antara gamification dan repurchase intention di Shopee sebagai platform e-commerce.